Effect of stretching-bending deformation and aging treatment on phase transformation behavior and superelasticity of Ti-50.8 at.% Ni alloy. (February 2021) - Liu, Shan; Zhu, Jie; Lin, Yao; Wang, Guangchun; Wang, Xiebin
Abstract: In order to improve the functional stability of Ti-50.8 at.% Ni alloys, a new plastic deformation method and device suitable for sheets or wires was developed in this work, called "stretching-bending deformation (SBD)". After SBD process, aging treatments were carried out at various temperatures (523–823 K) and various durations (0.5–12 h) to explore the effects of SBD process and aging treatment on the phase transformation behavior and superelasticity of NiTi alloys. The results indicate that the repeated stretching-bending process is an effective method to improve the functional stability of NiTi alloys, which introduces a certain amount of dislocations and refines the grain size from 9.1 μm in as-annealed state to 3.2 μm in the state after 15 SBD passes. After repeated SBD treatment, the martensitic transformation occurs in a wide temperature range, and the phase transformation peak becomes wider. Aging at 623 K for 0.5–1 h after 7 SBD passes helps to improve the functional stability. This is due to refined grains with an average grain size of 5.4 μm and favorable dislocations introduced by SBD and nanoscaled Ni4 Ti3 precipitates (<15 nm) induced by aging. Highlights: The method of stretching-bending deformation (SBD) suitable for NiTi sheets or wires is proposed. SBD process refines the average grain size from 9.1 μm to 3.2 μm through 15 passes. Favorable dislocations are introduced by SBD and nanoscaled Ni4 Ti3  precipitates ( < 15 nm) are induced by aging. The superelasticity is improved after 7 SBD passes and aging treatment at 623 K for 0.5-1 h.